Major Depression Reflected In Jodie Foster's The Beaver Movie (2011): A Psychoanalytic Approach - Veranita, Desi; , Dr. Phill. Dewi Candraningrum, S.Pd, M.ED; , Drs. H. Abdillah Nugroho, H.Hum (2013)
The research investigates how the major character suffers a major depression in his personality. Therefore, the study analyzes the movie based on structural elements of the movie with psychoanalytic approach. The object of the study is the personality of the major character of The Beaver Movie. The data sources of the research are library and literary data. Those are divided in two categories, primary data sources and secondary data sources. The primary data source is the movie itself and the secondary data are the other sources related to the movie. The technique of the data collection of the study is library research. The technique of the data analysis is descriptive analysis. The outcome of the study shows human suffering of major depression in their personality. It is reflected in the major character's personality when he must run up his company which almost bankrupt, then during he suffers a major depression, he cannot communicate with the others until he finds a beaver hand puppet as a tool to communicate with the others. Moreover, his major depression also reflected in his suffering when he really needs his family to recover him from the depression.